(untitled) (Research, Society and Development, 2022)
Myocarditis is an inflammatory heart disease that can occur as a consequence of infections (predominantly by viruses, but also by other infectious agents, including bacteria, protozoa and fungi), exposure to toxic substances (alcohol and drugs) and activation of the immune system. included among secondary cardiomyopathies in the 1996 classification of the World Health Organization. The present study aims to report the experience of health professionals in monitoring a patient with acute myocarditis, from the first day of admission to discharge. This is an experience report of a critical-reflective approach with a descriptive and comprehensive approach on a case experienced in the city of Niteroí - RJ, in a private hospital, about a patient with an initial suspicion of Coronary Artery Disease (CAD), the diagnosis of Acute Myocarditis (AM) was later confirmed in August 2019. The presentation of acute myocarditis is extremely variable and often subclinical, which can lead to acute complications or progress relatively asymptomatically to chronic heart failure. The gold standard for the diagnosis of myocarditis is still positive endomyocardial biopsy, an invasive procedure that requires a high pre-test clinical probability and a low risk/benefit ratio to be performed. However, the combination of measuring troponin levels and cardiac magnetic resonance imaging has made the diagnosis of MA possible with sufficient accuracy for uncomplicated forms. There are still gaps in understanding the pathogenesis and diagnostic and therapeutic options for myocarditis.